Integrated Multidisciplinary Management of Pediatric Diabetic Ketoacidosis: Nursing, Emergency Medical Services, Social Work, and Safety Systems Across the Care Continuum - Al-Mutairi, Khaled Lafi Abdulkarim; Fahad Bunaydir Shulaywih Almutairi; Mjaed Metaib Atek Almutairi; Fatimah Mohammed Salh Alamri; Najmah Abdullah Aldandan; Abdulaziz Mohammed Aqdi; Abdullah Madsus Alanazi; Bader Abdulhamid Mohammed Alharbi; Mohammed Faris Alqahtani; Fahad Abdul Aziz Alsaedi; Zamzam Ali Sahli (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Diabetic ketoacidosis (DKA) is a life-threatening metabolic emergency characterized by hyperglycemia, ketosis, and metabolic acidosis. Pediatric patients are particularly vulnerable due to limited physiological reserves and higher risk of cerebral edema. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To provide an integrated, multidisciplinary approach for managing pediatric DKA across emergency, nursing, social work, and safety systems, emphasizing evidence-based protocols and interprofessional collaboration. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review synthesizes current guidelines and literature on pediatric DKA, detailing pathophysiology, epidemiology, diagnostic criteria, and treatment strategies. It highlights the roles of emergency medical services, nursing care, and psychosocial interventions in optimizing outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> DKA incidence remains significant, with up to 30% of children presenting in DKA at initial diabetes diagnosis. Mortality rates are low in high-resource settings (0.15–0.31%) but cerebral edema accounts for most fatalities. Effective management requires early recognition, controlled fluid resuscitation, continuous insulin infusion, proactive electrolyte replacement, and vigilant neurological monitoring. Multidisciplinary coordination reduces complications and recurrence risk, particularly in adolescents where psychosocial factors often drive repeated episodes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pediatric DKA demands rapid, protocol-driven care integrated with education and prevention strategies. Interprofessional teamwork and structured communication are essential to minimize morbidity and mortality.